قرآنی سزاوں کی حکمتیں عصرِ حاضر کے تناظر میں؛ ایک تجزیاتی مطالعہ: The Wisdom of Qur'anic Punishments in the Contemporary Context: An Analytical Study - Khalida Farrukh, (Al-Amīr Research Journal for Islamic Studies, 2024)
Islam offers a comprehensive code of conduct that governs all aspects of human life, providing guidance through a detailed system of rules and regulations. The Holy Qur'an serves as the foundational curriculum for this ethical framework, established by Allah Almighty, the Supreme Being. All creations are bound to follow His divine commandments, which were exemplified by the life of the Prophet Muhammad ﷺ and faithfully observed by his companions. Islam is a complete and timeless religion, offering solutions to all human needs and challenges. Its teachings are not confined to a specific era but remain relevant until the Day of Judgment. The Qur'an clearly defines the paths of good and evil and sets boundaries for the welfare of both worldly life and the hereafter. Penalties are prescribed for those who transgress these limits, ensuring social order and justice. This research explores the benefits of adhering to these divine commandments and the consequences of violating them. The Qur'anic directives are designed to safeguard Islamic society from chaos and prejudice, fostering a balanced and harmonious community. Keywords: Code of Conduct, Commandments, Boundaries, Penalties, Societal Harmony, Chaos, Prejudice